Identification of candidate genes and development of KASP markers for soybean shade-tolerance using GWAS - Jia, Qianru; Hu, Shengyan; Li, Xihuan; Wei, Libin; Wang, Qiong; Zhang, Wei; Zhang, Hongmei; Liu, Xiaoqing; Chen, Xin; Wang, Xuejun; Chen, Huatao (Frontiers in Plant Science, 2024)
Shade has a direct impact on photosynthesis and production of plants. Exposure to shade significantly reduces crops yields. Identifying shade-tolerant genomic loci and soybean varieties is crucial for improving soybean yields. In this study, we applied a shade treatment (30% light reduction) to a natural soybean population consisting of 264 accessions, and measured several traits, including the first pod height, plant height, pod number per plant, grain weight per plant, branch number, and main stem node number. Additionally, we performed GWAS on these six traits with and without shade treatment, as well as on the shade tolerance coefficients (STCs) of the six traits. As a result, we identified five shade-tolerance varieties, 733 SNPs and four candidate genes over two years. Furthermore, we developed four kompetitive allele-specific PCR (KASP) makers for the STC of S18_1766721, S09_48870909, S19_49517336, S18_3429732. This study provides valuable genetic resources for breeding soybean shade tolerance and offers new insights into the theoretical research on soybean shade tolerance.